SIMULATION OF MEMORY CACHE - Ruiz L., Edgar (2003)
This article presents a program simulating the Cache Memory, by considering the system's success percentage and average access time.The program finds the Cache Memory's optimal size with regard to the RAM Memory size, which can be used as a valid criterion in designing both kinds of Memory within a computer.